The normative condition of the constitution and the cassation resorce. - Ruiz Abril, Karina Marianela; Cabrera Vélez, Juan Pablo; Flores Pillajo, Robert Enrique (Revista Universidad de Guayaquil, 2018)
The main goal of this job is to make a doctrinal, legal and critical analysis regarding to cassation resources into justice administration operability, according to current ecuadorian regulations that are consagrated into the "Código Orgánico General de Procesos" (General Organic Code of Processes), since this legal instrument includes several formal requirements that cause cassation resource to be denied due to lack of complience of certain formalities, resulting inaccepatable the lack of justice due to this issue that being opposed to the end section of the article 169, of the Judicial Function procedural system principals declaration, included into the Republic Constitution first
Keywords: Appeal; Cassation; Constitution; Legal Security; Normative Condition; Law